2013
DOI: 10.1155/2013/245349
|View full text |Cite
|
Sign up to set email alerts
|

Use of Dietary Supplements among Professional Athletes in Saudi Arabia

Abstract: The objective of this study was to understand the usage patterns of dietary supplements among professional athletes in Saudi Arabia. The survey consisted of sixteen questions divided into four categories: use of supplements, reason for consumption of supplements, personal beliefs about supplements, and behavior. The questionnaires were given to the three teams residing in Riyadh: Al Hilal, Al Nasr, and Al-Shabab. Out of the 105 athletes surveyed, we found that only 98 are currently taking dietary supplements a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
88
2
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(116 citation statements)
references
References 16 publications
11
88
2
7
Order By: Relevance
“…Consistent with the results of other studies [8,12,16], we found that coaches are the primary source supplement recommendation for most athletes, and dietitians were their second main source of information, corroborating the findings among Saudi Arabian athletes [26] and Brazilian cyclists [20]. However, in most studies cited here, dietitians are not among the main three information sources [5][6][7]18].…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the results of other studies [8,12,16], we found that coaches are the primary source supplement recommendation for most athletes, and dietitians were their second main source of information, corroborating the findings among Saudi Arabian athletes [26] and Brazilian cyclists [20]. However, in most studies cited here, dietitians are not among the main three information sources [5][6][7]18].…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies showed that athletes increasingly demonstrated sports performance as a major factor for supplementation usage and not only for health-related issues 5,6,11,12,14 .…”
Section: Reasons For Not Taking Supplementsmentioning
confidence: 99%
“…These products may contain vitamins, minerals, herbs or botanicals, amino acids and substances like enzymes, organ tissues, glandular and metabolites, extracts or concentrates under the form of tablets, capsules, liquids, powders, bars, soft gels or caps gels 2,3,7,[12][13][14] . Therefore, there is a range of supplements available with different and specific objectives 1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frequency, quantity and reasons of supplement consumption were assessed using a validated questionnaire (3) . Nutrient intake was assessed by a validated 3 day food diary and analysed using dietary assessment software Microdiet.…”
mentioning
confidence: 99%